Cultural differences in food detection - Wataru Sato; Krystyna Rymarczyk; Kazusa Minemoto; Sylwia Hyniewska (Scientific Reports, 2020)
Abstract The ability to detect food plays an indispensable role in our survival and wellbeing. Previous psychological studies have revealed that food is detected more rapidly than non-food items. However, whether the detection of food could be modulated by cultural factors remains unknown. We investigated this issue in the present study using a visual search paradigm with Polish and Japanese participants. Photographs of international fast food, domestic Japanese food, or kitchen tools were presented alongside images of non-food distractors (cars). Participants were asked to judge whether the stimuli were all identical or not. The reaction time data showed that participants from both cultures detected food more rapidly than kitchen tools. Japanese participants detected fast food more rapidly than Japanese food, whereas Polish participants did not display such differences between food types. These results suggest that rapid detection of food is universal, but is modulated by cultural experiences.